Share Split Effect On Trading Volume Activity and Abnormal Return In Indonesia - Najwa Fulki Assyifa; Indah Yuliana; Maretha Ika Prajawati (Jurnal Inovasi Pendidikan Ekonomi, 2025)
This research aims to identify and analyse if there is the difference in Trading Volume Activitiy and abnormal returns pre and post-share split event. The sample for this research consists of firms listed on IDX that have implemented a share split in 2019-2024. The research method used was the Shapiro-Wilk test for normality and the Wilcoxon signed rank test for difference between two variables. SPSS 27 software was used for data processing. Based on the outcomes of the Wilcoxon Signed Rank Test, it was found that there is a disparity in Trading Volume Activity prior to subsequent to the share split, which was indicated by an enhancement in the Trading Volume Activity value. For abnormal returns, differences were found pre and post share split, which was indicated by a positive abnormal return post share split.